121k views
2 votes
Helppppppppp pleaseee ASAP ​

Helppppppppp pleaseee ASAP ​-example-1
User Dutts
by
5.2k points

1 Answer

3 votes

Answer:

3

Explanation:

Given that:

Larger square is a dilation of smaller square

Dimension of smaller square (5 - 3) units by (5 - 3) units = 2 by 2

Dimension of larger square (7 - 1) units by (7 - 1) units = 6 by 6

Hence, the scale factor used to create the larger square from the smaller square will be:

Scale factor (x) * side of smaller square = side of larger square

x * 2 = 6

2x = 6

x = 6/2

x = 3

Hence, scale factor used to generate larger square is 3

User Hiren
by
5.2k points